Frequency self-adaptive plate spring-shock absorber - MITSCH FRANZ (2022)
The invention relates to a vibration damper or a vibration damper which can be adapted over a certain range to an active disturbance frequency of a component to be damped or of a vibration system to be damped by means of a device (2) consisting of a plurality of stacked, in particular shaped or curved leaf springs (2.1), wherein the position of the damper mass (1, 34) changes substantially only slightly. In particular, the invention relates to a shock absorber that functions in one and in two dimensions. The vibration damper according to the invention is suitable in particular for devices, vehicles and machines which are subject to frequent changes in rotational speed, as a result of which disturbance frequencies are often generated, which can be perceived in particular by the occurrence of solid-borne sound or other vibrations. 本发明涉及一种减振器或者振动阻尼器，其借助于由多个堆叠的、特别所成形的或者弯曲的板簧（2.1）构成的装置（2）能够在一定范围内与有待阻尼的构件或者有待阻尼的振动系统的起作用的干扰频率相适配，其中减振器质量（1、34）的位置基本上仅略微改变。本发明尤其涉及一种一维地和二维地起作用的减振器。按照本发明的减振器尤其适用于以下设备、车辆和机器，它们经受频繁的转速变化，由此